Shifting Patterns in Primary Care Telehealth Utilization Among Medicare Beneficiaries and Providers - Yunxi Zhang; Lincy S. Lal; Saurabh Chandra; John Michael Swint (Journal of Primary Care & Community Health)
Introduction: The COVID-19 pandemic accelerated telehealth adoption, but disparities in its utilization persist. This study examines primary care patient sociodemographic characteristics, telehealth utilization patterns, and provider adoptions before and during the pandemic. Methods: A retrospective cohort study analyzed data from Mississippi Medicare beneficiaries continuously enrolled in Parts A, B, and D who accessed primary care services from 2019 to 2021. Results: Among 201 677 Medicare beneficiaries accessing primary care, 1364 used telehealth before the pandemic, compared to 73 994 during the pandemic. Telehealth utilization shifted during the pandemic to younger, female, White beneficiaries, and those enrolled in Medicare due to disability or End Stage Renal Disease. During the pandemic, telehealth users exhibited higher Charlson Comorbidity Index and Social Vulnerability Index but lower Digital Divide Index scores compared to non-telehealth users. Telehealth was associated with more primary care visits, broader access, and higher continuity of care. Primary care physicians increased their share of telehealth services to 39%, while specialties such as neuropsychiatry and psychiatry showed the highest adoption rates, reaching 55% and 38%, respectively. Conclusions: Telehealth demonstrated a growing role in primary care during the pandemic. Future efforts must address digital divides and advance health equity when integrating telehealth into primary care services.